Variable DPP4 expression in multiciliated cells of the human nasal epithelium as a determinant for MERS-CoV tropism - Tim I. Breugem; Samra Riesebosch; Jingshu Zhang; Anna Z. Mykytyn; Lisette Krabbendam; Nathalie Groen; Sivana Baptista Varela; Debby Schipper; Petra B. van den Doel; Romy van Acker; Ralph Stadhouders; Mart M. Lamers; et al. (Proceedings of the National Academy of Sciences, 2025)
Transmissibility of respiratory viruses is a complex viral trait that is intricately linked to tropism. Several highly transmissible viruses, including severe acute respiratory syndrome coronavirus 2 and Influenza viruses, specifically target multiciliated cells in the upper respiratory tract to facilitate efficient human-to-human transmission. In contrast, the zoonotic Middle East respiratory syndrome coronavirus (MERS-CoV) generally transmits poorly between humans, which is largely attributed to the absence of its receptor dipeptidyl peptidase 4 (DPP4) in the upper respiratory tract. At the same time, MERS-CoV epidemiology is characterized by occasional superspreading events, suggesting that some individuals can disseminate this virus effectively. Here, we utilized well-differentiated human pulmonary and nasal airway organoid-derived cultures to further delineate the respiratory tropism of MERS-CoV. We find that MERS-CoV replicated to high titers in both pulmonary and nasal airway cultures. Using single-cell messenger-RNA sequencing, immunofluorescence, and immunohistochemistry, we show that MERS-CoV preferentially targeted multiciliated cells, leading to loss of ciliary coverage. MERS-CoV cellular tropism was dependent on the differentiation of the organoid-derived cultures, and replication efficiency varied considerably between donors. Similarly, variable and focal expression of DPP4 was revealed in human nose tissues. This study indicates that the upper respiratory tract tropism of MERS-CoV may vary between individuals due to differences in DPP4 expression, providing an explanation for the unpredictable transmission pattern of MERS-CoV.